The Effect of Listen-Read-Discuss (LRD) Strategy on Academic Achievement in History Among Eleventh-Grade Students. (Raparin Journal of Humanities (RJH), 2025)
This study aims to determine the effect of using Listen-Read-Discuss (LRD)strategy on the academic achievement of eleventh-grade students in History.The researcher followed the experimental approach, relying on two experimental designs (an experimental group and a control group).The research population consisted of all eleventh-grade female literary students at Arenko High School for 2024-2025. The study sample included 43 female students, randomly divided into two groups: the experimental group was 20 students, which they were taught using LRD strategy, and the control group was 20 students, which they were taught using the traditional method.The study's balance included previous year's History grades, Raven IQ test scores, parents' academic achievement, and students' ages in months. The researcher identified the educational material in Chapters 4 and 5 of the New and Contemporary History textbook. He developed behavioral objectives based on Bloom's levels (remembering, understanding, applying, and analyzing) which they were 130 behavioral objectives. He also prepared lesson plans for the academic subjects consisting of three daily lesson plans per week for each research group.The researcher has identified the data collection tools to achieve the research objectives via achievement test, which they were (50) items of multiple-choice type, and its validity was confirmed by presenting them to a group of experts, after calculating the ease or difficulty coefficient, discriminatory power and reliability of the test by using Cronbach’s alpha coefficient showed (0.87), which is a high rate, and thus the final test consisted of 43 items.After the end of the experiment, which lasted 12 weeks, the researcher applied the tools to the study sample. After collecting and analyzing the data using the Statistical Package for the Social Sciences (SPSS), the researcher reached this result, there were statistically significant differences at the level of (0.05) between the mean scores of the two research groups in the academic achievement test in favor of the experimental group.In light of the study results, the researcher reached a number of conclusions, recommendations and suggestions.